Antihypertensive and antihyperlipidemic activities of thymoquinone in l-name hypertensive rats - Azzubaidi, Marwan Saad; Noor, Noriah Mohd; Mizher, Hussam A. (Wolters Kluwer, 2015)
Objective: of this study was to evaluate the antihypertensive potential of Thymoquinone TQ and to investigate the underlying mechanism of action.